Modeling of Li-ion Battery Management System for Unmanned Aerial Vehicles - Kaya, Merve Nur; Bayrak, Zehra Ural (My University, 2024)
Nowadays, systems that use more electricity in aircraft are increasing due to harmful gas emissions. This increase has created the need to store electrical energy and accelerated the trend towards battery technologies. Since energy storage in batteries occurs as a result of chemical reactions, problems may occur that will damage the battery group or the entire system. These problems are caused by high current, voltage, and temperature, which affect the reaction rate during battery charging/discharging. A Battery Management System (BMS) is needed to prevent problems and to use the required electrical energy safely. In this study, it is aimed to meet the energy needs of the system in a controlled manner by disabling only the damaged cell in case of problems that may occur in the cells in the battery. For this purpose, a model of an Unmanned Aerial Vehicle (UAV) system been created by adding a BMS block to each cell to control the battery cells. The BMS model is realized based on the cell temperature, the State of Charge (SoC) value of the cell, and the output voltage values of the cell. The UAV system is modeled using MATLAB/Simulink environment. Thanks to the proposed BMS, in case of a problem that may occur in any cell in the battery, that cell will be disabled and the required energy will be met through the remaining cells. It is observed from the results obtained that when the cell parameters become normal, it continues to feed the system again.
Keywords: Battery; Li-ion; battery manegement system; UAV.